A review of the Tachinus longicornis-group of the subgenus Tachinoderus Motschulsky (Coleoptera: Staphylinidae: Tachyporinae) from China - Chang, Yuan; Li, Li-Zhen; Yin, Zi-Wei; Schülke, Michael (Zootaxa, 2019)
The Chinese species of the Tachinus longicornis-group of the subgenus Tachinoderus Motschulsky are reviewed with six species being treated, of which five are described as new: T. bilobus Chang, Li, & Yin sp. nov. (Hubei, Sichuan), T. centralis Chang, Li, Yin & Schülke sp. nov. (Shaanxi, Hubei, Chongqing, and Sichuan), T. curvipennis Chang, Li, & Yin sp. nov. (Hubei), T. lobutulus Chang, Li, & Yin sp. nov. (Yunnan), and T. tangliangi Chang, Li, Yin & Schülke sp. nov. (Yunnan; Thailand: Chiang Mai). Numerous new records are provided for T. ohbayashii Li, Zhao & Sakai, a species originally described from West Tianmu Mountain, Zhejiang. An identification key and a distributional map for the Chinese species are given.